A Framework of Successful E-Business Incubator for Indonesian Public Universities - Gozali, Lina; Masrom, Maslin; Haron, Habibah Norehan; Zagloel, Teuku Yuri M (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. In many developed countries, many business incubators take part to help starts-up company to develop their own business; especially the baby born business cannot compete with the giant industries that have become the old business players. Universities play an important role in motivating young graduates to become technology entrepreneur. Unemployment in Indonesia is still the main issue for the government program to increase welfare in the future. In year 2014 the data from Statistic Center of Indonesia state that Indonesia has 4% unemployment from Indonesiaâ€™ work generation. In Indonesia, incubators has been developed since 1992 initiated by the government, Cooperative Department and also universities. This effort continued in 1997 when there was a program called the Development of Entrepreneurship Culture in universities, and of its activity was New Entrepreneur Incubator. The objectives of the research are to investigate the success factor for e-business incubator, and to propose and develop a framework for successful e-business incubator for public universities in Indonesia. Research location is in Indonesia for the public universities that have their e-business incubator. This research will conduct quantitative and qualitative analyses based on data collection from incubator managers and business founders in Indonesia. The result of this research is a framework for successful e-business incubator in Indonesian public universities.Keywords: E-business incubator, Public university incubator, Successful e-business incubator, Framework, IndonesiaÂ